Applying foresight analysis towards the development of regional policy and strategic priorities for climate-resilient agriculture and food systems in West and Central Africa - Chesterman, Sabrina; Neely, Constance; Segnon, Alcade C.; Parramon-Gurney, Marie; Fuller, Emma-Jane; Lamien, Niéyidouba; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
In West and Central Africa (WCA), climate change threatens multiple aspects of farmers’ livelihoods, agri-food systems, and the natural resource base, requiring technical skills to consider risks and uncertainties and plan to adapt to the future. The West and Central African Council for Agricultural Research and Development (CORAF) identified foresight analysis as a pillar of its CORAF’s 2018-2027 Strategic Plan to build consensus on research priorities for building resilience to climate change impacts while considering complexity and uncertainty. Through its West Africa cluster, the Accelerating Climate Change Research in the CGIAR (AICCRA) in collaboration with CORAF developed the capacity of 12 experts on foresight analysis tools and facilitation skills from nine countries from West and Central Africa to serve as a Community of Practice (COP) of experts as means of mainstreaming foresight analysis in the region. To ground the training in an agri-food priority context, the newly trained COP and AICCRA specialists facilitated a foresight application with 23 technical thematic experts from across WCA to co-design a plan for coordinating preparedness and response to pest and disease outbreaks with a climate change lens. The foresight process undertaken included analyzing trends and evidence, understanding relevant stakeholders engaged before, during, and after pest and disease outbreaks, developing a shared vision of coordination responses, and creating scenarios representing alternative futures based on drivers and uncertainty. The foresight analysis concluded with designing transformative pathways to enhance the capacity for effectively addressing the risks presented by transboundary pests and diseases. The overall effort resulted in a deeper understanding of the value of foresight and a capacitated COP of foresight facilitators and a preliminary roadmap for a regional preparedness and response plan for pest and disease outbreaks.